Pengaruh Metode Jarimatika Pada Operasi Aljabar Terhadap Prestasi Belajar Siswa Kelas III SD Negeri 1 Baadia - Herlawan Herlawan; Sukmayanti Sukmayanti (Jurnal Akademik Pendidikan Matematika, 2026)
The problem statement in this research is, Is there any effect of the jarimatika method on algebraic operations on the learning achievement of third-grade students at SD Negeri 1 Baadia?. This research aims to determine the effect of applying the jarimatika method on algebraic operations on the learning achievement of third-grade students at SD Negeri 1 Baadia. This research uses a quantitative approach with a quasi-experimental design. The population in this study were all class III students at SD Negeri 1 Baadia which consists of two classes, namely class III A and class III B, with a total population of 39 students. The sample in this study is the same as the population, namely class III A with 21 students as the control class and class III B with 18 students as the experimental class. The instruments used were tests on addition, subtraction, and multiplication to assess the learning process and student behavior using the finger arithmetic method. The data were analyzed using descriptive analysis, prerequisite analysis (normality and homogeneity analysis), and Independent Sample T-Test analysis. The results of this study are the analysis of normality and homogeneity tests that the data are normally distributed and homogeneous, followed by hypothesis testing estimated with a hypothesis test (Independent Sample T-Test) with equal variances assumed. Based on the analysis results, tcount=2.232 ttable = 2.026 with a significance value of 0.032 <0.05, so Ho is rejected and H₁ is accepted based on the hypothesis acceptance criteria. Therefore, the researcher concludes that there is an effect of using the jarimatika method in algebraic operations on the learning achievement of third-grade students at SD Negeri 1 Baadia.